Supplementary datasets to the article "Botanical extracts for insect management: lessons from participatory research in the peri-urban horticultural systems of central Argentina" [Conjunto de datos] - Arguello Caro, Evangelina Beatriz (2024)
11 tablas en formato .xlsx